Challenging RSD clients' preferences for foreign service providers - Pangilinan, C (Refugee Studies Centre, University of Oxford, 2012)
Organisations that provide legal services to refugees and asylum seekers face the challenge of responding ethically to clients' requests to be assisted by foreigners as opposed to by nationals in country offices.